Analysis of Efficiency of Human Resource Management Evaluation Model Based on SOM Neural Network. (23rd March 2022) - Liu, Xu; Wang, Xuewen; Du, Xiaowei; Gu, Peng
Abstract : The success of human resource management is directly related to whether enterprises can stand in the fierce market competition. In the actual operation of enterprises, the human resource management faces various risks. Here, we take the human resource management evaluation standard as the research object and establish the human resource management benefit evaluation model through a SOM neural network. The training, studying, and testing processes of the model are performed. Besides, the human resource management evaluation system is built on the basis of this model. The evaluation research on the efficiency of human resource management has a good influence in many aspects. Researchers have tried to decipher the "black box" relationship between human resource management and organizational benefits, and an effective human resource management evaluation tool is obtained. This model involves both theoretical construction and empirical research. It is of great significance to summarize the progress and existing problems of current research and abroad and put forward some suggestions for future research.